Makna Kebahagiaan Pada Karyawan Wanita Usia Madya Di Kumala Laundry Kota Banjarmasin - Sa'adah, Nangimatus; Faridah, Siti; Hairina, Yulia (Jurnal Al-Husna, 2021)
Employee happiness greatly affects their performance. With higher happiness, middle-aged employees will be more optimal so that they can make a positive contribution to their family and the surrounding environment. The purpose of this research is to know a picture of happiness and to identify the happiness factor felt by middle age female employees at Kumala Laundry, Banjarmasin City. This research is field research, qualitative research methods. The research subjects were 2 women working at Kumala Laundry in Banjarmasin City. Data collection techniques using interviews and observations. The results obtained showed that happiness in middle age female employees was in the cognitive and affective aspects. From the cognitive aspects of subjects S and A have different life satisfaction. The affective aspect of the two subjects also had different results, but they both accepted and were grateful for what they got. The factors that affect the happiness of subject S are money, marriage, social life, health and religion, while subject A is money, marriage, age, health and religion